Comparative study on sensitivity of different physiological properties of Spirodela polyrrhiza (L.) Schleiden to Cr (VI) treatments - Oláh, Viktor (Acta Biologica Szegediensis, 2008)
The aim of this study was to compare the sensitivity of various growth and biochemical traits in axenic S. polyrrhiza cultures under chromium (VI) stress. Frond number, fresh weight of plants, number and elongation of roots, frond area, photosynthetic pigment content and anthocyanin accumulation of plants responded sensitively to Cr (VI) treatments in the applied concentration range. Anthocyanic abaxial leaf surface and anthocyanin content of plants showed extremely high sensitivity to Cr (VI) reaching multifold levels to that of control values.